2021
DOI: 10.1021/acsaem.1c01767
|View full text |Cite
|
Sign up to set email alerts
|

Polaron-Assisted Charge Transport in Li-Ion Battery Anode Materials

Abstract: Lithium-ion batteries are without a doubt a key technology in the coming energy revolution. It is thus all the more surprising that one of the more prevalent Li battery anode materials, reduced lithium titanium oxide (LTO, Li4Ti5O12), is still poorly understood on a microscopic level. While recent theoretical and experimental evidence suggests that a polaron hopping mechanism is responsible for the increased electronic conductivity of reduced LTO, no such explanation exists for the concurrent improvements to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…It destabilizes the formation of polarons at the V 2 O 5 interface. Such less stable polarons exhibit a smaller electron–lattice interaction, which could improve charge transport kinetics at the interface . The details of these calculations are discussed as follows.…”
Section: Resultsmentioning
confidence: 99%
“…It destabilizes the formation of polarons at the V 2 O 5 interface. Such less stable polarons exhibit a smaller electron–lattice interaction, which could improve charge transport kinetics at the interface . The details of these calculations are discussed as follows.…”
Section: Resultsmentioning
confidence: 99%
“…47 Oxygen deficiency is associated with the presence of V O 2+ . 48 Hightemperature thermal annealing, electron bombardment, and UV irradiation under oxygen-deficient or vacuum conditions also generate oxygen defects. 26,49 Qiu et al have found that the hydrogenation process causes crystalline dislocation and produces V O 2+ throughout the bulk and surface of the rutile TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Several additional features influencing ion mobility have been discussed in the literature, including lattice dynamics, phonon frequencies, and amplitudes [3,[15][16][17]. The polarizability of atoms, categorized as a chemical feature, has also been suggested as a potential correlate to ion migration [18,19]. The crystalline lattice framework and structural features can play a role as well, with coordination geometries enhancing cation site stability and increasing migration barriers [20,21].…”
Section: Descriptors For Ion Mobilitymentioning
confidence: 99%